Juros sobre o capital próprio função e efeitos na tributação da renda - Motta, Elaine Cristina de Oliveira (2021)
The research aims to analyze the function and the effects of interest on net equity (JCP) in the taxation of corporate income. Starting with the history of the current legislation, we report the procedures and requirements for the payment of interest on net equity and the respective tax effects. In addition, we analyze the related themes, which are the capital structure of companies and their importance, the taxation of corporate income and tax incentives rules. Having established the theoretical bases, considering the corporate income tax system, the relationship between interest on net equity and this system and tax incentives, the purpose will be to verify whether interest on net equity is some kind of tax incentive, as is common to be referenced in political and social forums. Finally, the mechanism will be compared to some similar mechanisms in foreign countries (Allowance for Corporate Equity) and corresponding treatment in order to add some different international experience. Based on these studies, is possible to verify despite the importance of interest on net equity for tax corporate purposes, it also has effects from the perspective of attracting investments and maintaining the economy.